Systematic Literature Review: Strategies for Active and Creative Learning in Elementary School Physical Education - Artiluhung, Rea Restiuna; Mahendra, Agus; Yulianto, Ari Gana; Aman, Mohd Salleh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Physical education in elementary schools has an important role in developing children's physical, mental and social development. This research investigates innovative teaching strategies in physical education in elementary schools, with the aim of improving motor skills, increasing physical fitness, and fostering a healthy lifestyle among children. The method used is Systematic Literature Review (SLR) with due diligence articles using MMAT to identify articles during the screening and data extraction stages. Of the 210 articles that were first downloaded, the final 33 articles underwent inclusion and exclusion screening based on certain criteria to analyze various approaches, including technology integration, educational games, skills-based learning, active student participation, and inclusive practices. Findings demonstrate the effectiveness of these strategies in creating engaging and inclusive learning environments. This research highlights the importance of going beyond traditional game-based approaches and exploring more diverse strategies to meet students' individual interests and talents